GAME TECHNOLOGIES IN THE PROCESS OF TEACHING MATHEMATICS TO PRIMARY SCHOOL STUDENTS: AN ERGONOMIC DIMENSION - Н. Карапузова; Є. Починок; О. Палеха (Естетика і етика педагогічної дії)
The article highlights some theoretical aspects of the usage of game technologies in primary school. The expediency has been determined and the range of target orientations of game technologies in the process of teaching mathematics to primary school students has been considered. Features of game activity in the modern educational environment of primary school are characterized. Ergonomic pedagogical conditions for the effective usage of didactic games in the process of learning the mathematical educational field are outlined. They are the following: taking into account the cognitive features of the education of students of the digital generation in the content of the structural components of didactic games; the use of inter-subject connections, with the aim of focusing didactic games on students’ mastery of generalized techniques of cognitive activity; ensuring children’s functional comfort in the process of game activities.